Risk Factors for Depressive Disorders after Coming through COVID-19 and Emotional Intelligence of the Individual - Zhylin, Mykhailo; Makarenko, Svitlana; Kolohryvova, Nadia; Bursa, Andrii; Tsekhmister, Yaroslav (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: COVID-19 has caused many new challenges for humanity worldwide. The pandemic united society from different regions of the planet in the experience of experiencing the epidemic, particularly complications after the disease, including the development of depression and increased anxiety. The study aimed to identify risk factors for depression among people who came through moderate and severe coronavirus infection and to substantiate the role of emotional intelligence as a factor that prevents depressive disorders. Methods: The author’s questionnaire, Beck’s Depression Inventory (BDI-II), Emotional Intelligence Test (EmIn), and narrative analysis were used for this purpose. Results: The separate groups of respondents, distributed according to their socio-economic status, were studied for their level of general emotional intelligence. High indicators of emotional intelligence of public sector employees who are in constant social interaction were recorded. A group of entrepreneurs focused on solving pragmatic financial and economic problems had low emotional intelligence. Severe depression symptoms were also the most common among a group of entrepreneurs. A decreased level of emotional intelligence in groups of female public sector employees and increased depressive symptoms were empirically found. The physiological factor was the most significant in contributing to depression. Conclusions: The main advantage of the study is the empirical justification of the role of internal anti-stress regulation mechanisms, with the development of emotional intelligence as one of the tools. Prospects for further research include improving diagnostic tools and studying the longer-term consequences of coronavirus disease, particularly in different groups of respondents.